Cutaneous manifestations of polycystic ovary syndrome: A cross-sectional clinical study - Mohammad Abid Keen; Iffat Hassan Shah; Gousia Sheikh (Wolters Kluwer Medknow Publications, 2017)
Background: Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders in women, affecting 5-10% of reproductive-aged women. The dermatologic manifestations of hyperandrogenism, chiefly hirsutism, acne vulgaris, androgenic alopecia, and acanthosis nigricans, are among the cardinal manifestations of PCOS. Aim: To study the incidence and prevalence of various cutaneous manifestations in patients with PCOS and to correlate these skin manifestations with hormonal changes. Settings and Design: This study was conducted at a dermatology centre over a period of 1 year from November 2012 to 2013. Materials and Methods: The present study included 100 women diagnosed to have PCOS. Hormonal analysis as well as radiological assessment was done in all the cases. Cutaneous manifestations were ascertained and inferences were drawn. Statistical Analysis: Statistical analysis was carried out by the Chi-square test and independent samples t-test. Statistical significance was determined at a level of P < 0.05. Results: In our study, the prevalence of hirsutism, acne, female pattern hair loss, acanthosis nigricans, seborrhea, striae and acrochordons was 78%, 48%, 31%, 30%, 29%, 13%, and 9%, respectively. Conclusion: Dermatologic manifestations of PCOS play a significant role in making the diagnosis and constitute a substantial portion of the symptoms experienced by women with this syndrome.